PRINCIPLES OF COMPILING AN ENGLISH-UZBEK DICTIONARY OF MINING TERMS (Academicia Globe: Inderscience Research, 2023)
The article describes the problems of developing the principles of the Uzbek-English dictionary of mining terminology. The main research methods are the analysis of literature on the research topic and the statistical method. In the study, the concept of mining terminology is clarified, the difference between the concepts of graphic and lexicographic terms is given, and the main principles of material selection for the dictionary of mining terms are given.